Effectiveness of sire evaluation based on actual and predicted first lactation 305 day milk yield in Rathi Cattle - Manju Nehara,; Urmila Pannu,; G C Gahlot, (Journal of Livestock Biodiversity, 2025)
A total of 362 first lactation 305-day milk yield records of Rathi cows maintained at Livestock Research Station, Nohar and Bikaner over a period of 33 years (1985 to 2017) were analysed which are daughters of 31 sires with five or more progenies per sire. Rathi sires were evaluated on the basis of actual and predicted first lactation 305-day milk yield using single trait animal model (STAM) fitting restricted maximum likelihood (REML) method. The expected breeding value based on actual and predicted first lactation 305-day milk yield (PL305MY) were compared using Spearman’s rank correlation. The rank correlation between STAM-A (single trait animal model using actual first lactation 305-day milk yield) and STAM-P (single trait animal model using predicted first lactation 305-day milk yield) was observed 0.60 which showed significant association between ranks of sires based on actual and predicted milk yields. It was inferred that PL305MY may be used as criterion for sire evaluation earlier than actual FL305MY.